Planetary Geochemical Investigations Using Raman and Laser-Induced Breakdown Spectroscopy. Issue 9 (September 2014) - Clegg, Samuel M.; Wiens, Roger; Misra, Anupam K.; Sharma, Shiv K.; Lambert, James; Bender, Steven; Newell, Raymond; Nowak-Lovato, Kristy; Smrekar, Sue; Dyar, M. Darby; Maurice, Sylvestre
An integrated Raman spectroscopy and laser-induced breakdown spectroscopy (LIBS) instrument is a valuable geoanalytical tool for future planetary missions to Mars, Venus, and elsewhere. The ChemCam instrument operating on the Mars Curiosity rover includes a remote LIBS instrument. An integrated Raman-LIBS spectrometer (RLS) based on the ChemCam architecture could be used as a reconnaissance tool for other contact instruments as well as a primary science instrument capable of quantitative mineralogical and geochemical analyses. Replacing one of the ChemCam spectrometers with a miniature transmission spectrometer enables a Raman spectroscopy mineralogical analysis to be performed, complementing the LIBS chemical analysis while retaining an overall architecture resembling ChemCam. A prototype transmission spectrometer was used to record Raman spectra under both Martian and Venus conditions. Two different high-pressure and high-temperature cells were used to collect the Raman and LIBS spectra to simulate surface conditions on Venus. The resulting LIBS spectra were used to generate a limited partial least squares Venus calibration model for the major elements. These experiments demonstrate the utility and feasibility of a combined RLS instrument.